The median effective concentration of epidural ropivacaine with different doses of dexmedetomidine for motor blockade: an up-down sequential allocation study - Wan, Ji-Xiang; Lin, Chao; Wu, Zhi-Qiang; Feng, Duan; Wang, Yuan; Wang, Fang-Jun (Frontiers in Medicine, 2024)
Recent studies have shown that dexmedetomidine can be safely used in peripheral nerve blocks and spinal anesthesia. Epidural administration of dexmedetomidine produces analgesia and sedation, prolongs motor and sensory block time, extends postoperative analgesia, and reduces the need for rescue analgesia. This investigation seeks to identify the median effective concentration (EC 50 ) of ropivacaine for epidural motor blockade, and assess how incorporating varying doses of dexmedetomidine impacts this EC 50 value.Design: Prospective, double-blind, up-down sequential allocation study.Setting: Operating room, post-anesthesia care unit, and general ward.Interventions: One hundred and fifty patients were allocated into five groups in a randomized, double-blinded manner as follows: NR (normal saline combined with ropivacaine) group, RD 0.25 (0.25 μg/kg dexmedetomidine combined with ropivacaine) group, RD 0.5 (0.5 μg/kg 0.624% (95% CI, 0.550-0.728%) in the RD 0.25 group, 0.549% (95% CI, 0.456-0.660%) in the RD 0.5 group, 0.463% (95% CI, 0.408-0.527%) in the RD 0.75 group, and 0.435% (95% CI, 0.390-0.447%) in the RD 1.0 group.The EC 50 of the NR group and the RD 0.25 group were significantly higher than that of the RD 0.75 and the RD 1.0 groups, and the EC 50 of the RD 0.5 group was significantly higher than that of the RD 1.0 group.The EC 50 of epidural ropivacaine required to achieve motor block was 0.677% in the NR group, 0.624% in the RD 0.25 group, 0.549% in the RD 0.5 group, 0.463% in the RD 0.75 group, and 0.435% in the RD 1.0 group. Dexmedetomidine as an adjuvant for ropivacaine dose-dependently reduce the EC 50 of epidural ropivacaine for motor block and shorten the onset time of epidural ropivacaine block. The optimal dose of dexmedetomidine combined with ropivacaine for epidural anesthesia was 0.5 μg/kg.